Studies on calcium reduction of yttrium fluoride. (2nd January 2016) - Mukherjee, A.; Awasthi, A.; Krishnamurthy, N.
Abstract : The reduction of yttrium fluoride (YF3 ) by calcium in a molybdenum crucible was investigated. A visual observation technique was used to monitor the reduction process. It was observed that the reaction initiated immediately after the melting of calcium. Based on the results, a two-step reduction sequence was attempted. First, the charge was heated to 950°C to minimise the calcium loss by vaporisation and to ensure completion of reaction. The products were then fast heated to 1600°C for slag/metal separation. Molybdenum content of yttrium was found to be in a range of 3.5–4.75 wt-%, which is much lower than the equilibrium content predicted by Mo–Y phase diagram. The yttrium/molybdenum interface was studied using an electron probe microanalyser, which confirmed that the overall equilibrium was not reached, indicating the possibility of lowering the molybdenum contamination further by process optimisation.